2015
DOI: 10.1016/j.envpol.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transpiration on plant accumulation and translocation of PPCP/EDCs

Abstract: The reuse of treated wastewater for agricultural irrigation in arid and hot climates where plant transpiration is high may affect plant accumulation of pharmaceutical and personal care products (PPCPs) and endocrine disrupting chemicals (EDCs). In this study, carrot, lettuce, and tomato plants were grown in solution containing 16 PPCP/EDCs in either a cool-humid or a warm-dry environment. Leaf bioconcentration factors (BCF) were positively correlated with transpiration for chemical groups of different ionized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(63 citation statements)
references
References 39 publications
3
59
1
Order By: Relevance
“…The transpiration stream is considered as the main driving force for uptake and transport of pharmaceuticals from soil to plants (Dodgen et al, 2015). In this study, the three common soil water contents (75, 60 and 45 % of MWHC) did not have an apparent impact on the accumulation of pharmaceuticals in the radish tissues.…”
Section: Plant Uptakementioning
confidence: 68%
“…The transpiration stream is considered as the main driving force for uptake and transport of pharmaceuticals from soil to plants (Dodgen et al, 2015). In this study, the three common soil water contents (75, 60 and 45 % of MWHC) did not have an apparent impact on the accumulation of pharmaceuticals in the radish tissues.…”
Section: Plant Uptakementioning
confidence: 68%
“…As an example, an overall low root accumulation of acidic PPCPs, including naproxen, diclofenac, atorvastatin, gemfibrozil, and ibuprofen, was observed in a hydroponic study . However, an opposite phenomenon was observed by Dodgen et al (2015), who found that these acidic PPCPs were accumulated significantly more than basic or neutral PPCPs in plant roots. (Boxall et al, 2006;Calderón-Preciado et al, 2011;Carter et al, 2014;Eggen et al, 2011;Holling et al, 2012;Hu et al, 2010;Pan et al, 2014;Prosser et al, 2014a;Shenker et al, 2011;Wu et al, 2010;Wu et al, 2012b).…”
Section: Root Uptake Of Ppcpsmentioning
confidence: 70%
“…A number of studies have been performed under hydroponic conditions to evaluate the bioaccumulation potentials of PPCPs in plants and explore uptake mechanisms under simplified conditions (Bartha et al, 2010;Calderón-Preciado et al, 2012;Dodgen et al, 2013Dodgen et al, , 2015Herklotz et al, 2010;Redshaw et al, 2008;Shenker et al, 2011;Tanoue et al, 2012;Wu et al, 2013). The extent of PPCP uptake by plants is usually evaluated using bioconcentration factor (BCF), which is the ratio of the analyte concentration detected in the plant tissue to the spiked concentration in the growth medium.…”
Section: Ppcps In Plants Grown Under Hydroponic Conditionsmentioning
confidence: 99%
See 2 more Smart Citations